Perception of personal risk to COVID-19 in dentistry graduates from a peruvian university - Mendoza Cordova , Zenaida Olga (2023)
Objectives: Determine the perception of personal risk to COVID-19 in graduates of the dental school of a Peruvian university in 2022. Materials and Methods: An observational and cross-sectional design study was carried out on 118 graduates using simple random probabilistic sampling. The survey was sent virtually and validity (expert judgment) and reliability (Cronbach's Alpha 0.90) were evaluated. Results: A moderate perception of personal risk to COVID-19 was obtained, based on the Morton and Duck (2004) scale. 89.9% stated that this disease is serious, 88.2% considered dental practice as a personal risk, 81.3% indicated that they were in a job with risk of exposure, 33% considered that their mental health was altered due to the pandemic, 26.3% were worried about their mental health diagnosis and that it would influence their dental practice, 40.7% felt worried about the news and 72% felt safe after receiving the vaccine. A significant relationship was found between the perception of personal risk to COVID-19 with the work area (p=0.049). Conclusions: The perception of personal risk to COVID-19 was moderate in dental school graduates, there was no statistical association with the covariates.